Long-term visual outcome and its predictors in macular oedema secondary to retinal vein occlusion treated with dexamethasone implant. Issue 4 (11th June 2018) - Busch, Catharina; Rehak, Matus; Sarvariya, Chintan; Zur, Dinah; Iglicki, Matias; Lima, Luiz H; Invernizzi, Alessandro; Viola, Francesco; Agrawal, Kushal; Sinawat, Suthasinee; Couturier, Aude; Mehta, Aanchal; et al.
Abstract : Background: To evaluate the functional long-term outcome in patients with macular oedema (MO) secondary to central retinal vein occlusion (CRVO) and branch retinal vein occlusion (BRVO) treated with dexamethasone implant (DEX implant) and to identify its clinical predictors. Methods: A 24-month, retrospective, multinational, real-world study. Chart review of patients with either naïve or recurrent MO secondary to CRVO/BRVO treated with DEX implant, including best-corrected visual acuity (BCVA), central subfield thickness (CST), demographic baseline characteristics and details of any additional treatment during follow-up. Results: A total of 155 eyes (65 CRVO, 90 BRVO) from 155 patients were included. At 24 months, mean BCVA did not change significantly in CRVO (−2.1±24.5 letters, p=0.96) and BRVO patients (1.3±27.0 letters, p=0.07). A worse baseline BCVA (p<0.001), visual acuity (VA) gain ≥5 letters at 2 months (p=0.006) and no need for adjunctive intravitreal therapy after first DEX implant (p=0.001) were associated with a better final BCVA gain. Treatment-naïve patients (p=0.006, OR: 0.25, 95% CI 0.11 to 0.57) and those with a baseline CST≤400 µm (p=0.02, OR: 0.25, 95% CI 0.10 to 0.63) were identified as being less likely to need additional intravitreal therapy. Conclusion: Clinical baseline characteristics and the early treatment response were identified as possible predictors for long-term outcome and the need of adjunctive intravitreal therapy in MO secondary to BRVO/CRVO treated by DEX implant.